Alternatives for mitigating the environmental impact generated in the camales - López Ponte, Wilder Michel (2022)
The abattoirs are productive spaces with a significant impact on the environment and public health, due to the nature of the raw material and the waste generated during the processes. That is why the purpose of this work is to develop a categorization of the environmental impact of the waste generated in the slaughterhouses, to propose mitigation alternatives. This work is methodologically based on descriptive, explanatory, and sectional documentary research. Likewise, the Agricultural sector has a Solid Waste Management Regulation approved by supreme decree No. 016-2012-AG (MINAGRI, 2012), however, the adequacy of said standard is necessary, as indicated in the fifth final supplementary provision of Supreme Decree No. 014-2017-MINAM (MINAM, 2017), decree approving the Regulations of Legislative Decree No. 1278, Law on Comprehensive Solid Waste Management (MINAM, 2017). The results obtained allow us to describe the various waste generated, explain the causes of the environmental impact, and detail the mitigation measures, highlighting the value that can be given to this waste. Finally, it is recommended to continue with the investigations and generation of sectorial legal devices that allow to control and sanction non-compliance with environmental quality parameters.